STUDY OF POTENCY DEVELOPMENT OF MARIN ECOTORISM TANGAH ISLAND PARIAMAN CITY WEST SUMATERA PROVINCE - Setiawan, Ilham; Tanjung, Afrizal; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted in March - April 2018 in Tangah Island, Pariaman City, West Sumatera Province. The study aims to identify potential natural resources to be used as marine ecotourism, formulate strategies and assess the role of stakeholders in Pariaman City in developing Tangah Island. The method used in this research is survey method and station point determination by purposive sampling. The calculation result of Value of Conformity Index is 83.33 (Station I), 86.53 (Station II), 84.61 (Station III), 84.61 (Station IV). An assessment of the strengths, weaknesses, opportunities and threats of potential development of marine ecotourism of Tangah Island is obtained from observations at research sites, interviews and questionnaires. Pariaman city has the potential as a marine ecotourism area such as natural beauty of nature, culinary tour, cultural tourism, beach with white sand and interesting underwater scenery. The development of marine ecotourism object in Tangah Island can be done by 1) Spatial and area arrangement by establishing zonation system for marine tourism activities and activities undertaken by the community towards marine ecotourism activities and coastal environment management, 2) Creating job field and reducing poverty level and preserving nature, 3) Utilizing the potential of natural resources, history, culture, accessibility of the region to attract visitors through the development and development of marine tourism with the concept of ecotourism through the stages of promotion.Keywords: Potential, Marine Ecotourism, SWOT Analysis, Tangah Island